Transição ecológica: crianças no início da vida escolar e as mudanças de ambiente, atividades, relações e papeis - ALVÃO, Maureanna Cardoso (Universidade Federal do Pará, 2019)
Throughout life the individual undergoes changes in its way of thinking, doing and feeling, usually resulting from transitions experienced in childhood and the changes that underlie the exchange of roles and changing ecological environment. In this sense, it is understood that the concept of ecological transition having been made in the scope of a theory of human development applies to studies like this intends to investigate the perception that children have their insertion and adaptation to school as an ecological context which differs from the family environment. This research aimed to study the process of ecological transition that involves the connection between family and school microsystems from the point of view of children and their caregivers, by investigating the changes of environment, activities, roles and relationships that mark the beginning of school life. The specific aims were to investigate how children experience and perceive the processes of ecological transition characterized by their inclusion and participation in daily life in two different microsystems, but related - family and school, to identify factors that facilitate and hinder the process of adjusting to school and that mark the experience of this form of ecological transition from the point of view of children and their families and teachers; describe ecological transition processes experienced by children in the first year of their school life, identifying possible similarities and differences in their perception on grounds of age. 53 people participated in the survey, with forty-six children enrolled in the Children's House School St Agnes (ECCSI), four parents and/or guardian and three teachers. Besides the family environment (here considered as the place of residence) and school (internal dependencies school, especially the kids bedrooms , the staff room and classrooms), children (especially in the study of multiple cases) were observed in their path way to school and on their return home. Parents were interviewed in the staff room, as well as the male child dorm. Have teachers were interviewed in classrooms Garden I, and the staff room. Among the main results, it was found that, every day, during the journeys of going to school and back to the house the children demonstrated both feelings of bem-estar/alegria (involving the mother and other family members in daily routines , relationships started in the environment school) as mal-estar/tristeza (complaints of pain and other symptoms of illness, violence). With regard to the factors that facilitate and hinder the process of adjusting to school that were organized around the four cores of the bioecological model was observed to be the most frequent categories: person (living comfortable and positive emotions, and bodily manifestations physiological) changes, and process (positive attitude toward school and learning). Comparing the three selected cases, it was noticed that each of the children lived in a particular way the adaptation process at the beginning of school life, it is important to note how much resisted changes resulting from their stay in a new environment and their activities, relationships and roles. This study may be useful to expand knowledge about this and other ecological transitions experienced in childhood, especially the adaptation of the child at the beginning of school life.